Study on the optimum dietary energy level for laying Shao ducks - YIN Zhao-zheng; YU Dong-you; ZHU Chun-lei (浙江大学学报. 农业与生命科学版, 2000)
A grouped feeding trial, metabolism trial and egg quality mensuration for laying Shao ducks were conducted to determine the effects of five diets with different content of metabolizable energy (10.67 MJ·kg-1, 10.88 MJ·kg-1, 11.09 MJ·kg-1, 11.30 MJ·kg-1, 11.51 MJ·kg-1, respectively) in a same level of 17.5% crude protein on egg laying performance, feed protein utilization, energy metabolism, and egg quality. The results indicated that egg laying performance of ducks was high when fed diets with middle levels of 10.88-11.30 MJ·kg-1 metabolizable energy (ME), profit potential per duck was best in level of 11.09 MJ·kg-1. With the increase of dietary ME level, daily feed intake was gradually reduced. There was a significant correlation between them (r=-0.785, P<0.05); Ratio of nitrogen retention improved with the increase of dietary ME level, which in groups with 11.09 MJ·kg-1, 11.51 MJ·kg-1 levels were significantly higher than that with 10.67 MJ·kg-1 (P<0.05). Compared with the group fed 10.67 MJ·kg-1 ME, energy metabolism ratio significantly increased in groups with 10.88 MJ·kg-1, 11.09 MJ·kg-1 ME levels; Furthermore, egg weight was relatively high for those ducks at age of 38 weeks fed 10.88 MJ·kg-1, 11.09 MJ·kg-1 ME levels, and egg-shell thickness was ideal for groups containing 10.67 MJ·kg-1, 11.09 MJ·kg-1 ME. It was suggested that the optimum dietary metabolizable energy level for laying Shao ducks was 11.09 MJ·kg-1, with CP/ME ratio: 15.78 g·MJ-1.